The effect of seasonal variations on food consumption, dietary habits, anthropometric measurements and serum vitamin levels of University Students - Kucukerdonmez, Ozge; Rakıcıoglu, Neslisah (Progress in Nutrition, 2018)
Aim: The aim of this study was to examine the effect of seasonal variations on the dietary habits, food consumption, anthropometric measurements, physical activity and some serum vitamin levels of adult females.  Methods:The study was conducted during consecutive four seasons in October (autumn), January (winter), April (spring), and July (summer). After general information was obtained about the participants via questionnaire, their anthropometric measurements were taken, and individual records kept for 7-day individual food consumption and 3-day physical activity. Also, their body compositions (Body Stat 1500Ò) and resting metabolic rates (Ergospirometry-Cosmed K4b2) were measured.  Participant serum samples were analyzed for levels of vitamins A, E, β-carotene and 25-OH Vitamin D3. Subjects: Thirty-five healthy, young adult females between the ages of 19 and 24 were invited into a prospective research study. Results: Spring was found to be the season with the highest intake of energy and nutrients compared with other seasons  (p